2017
DOI: 10.21873/anticanres.11378
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Platelet–to–Albumin Ratio Predicts Prognosis of Patients with Pancreatic Ductal Adenocarcinoma After Pancreatic Resection

Abstract: The preoperative PAR is a novel significant independent prognostic index for DFS and OS in patients after pancreatic resection with curative intent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 26 publications
(34 reference statements)
0
55
0
1
Order By: Relevance
“…Many studies affirmed that ALB alone or based markers were correlated with survival in various cancers 23 , 25 - 27 . Similarly, ALB alone or based markers were confirmed as independent predictors of PDAC with poor survival 14 , 28 , 29 . ALP associated with ALB as a predictor had been applied into several other cancers 19 , 30 , however, the value of prediction in PDAC was still not identified.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Many studies affirmed that ALB alone or based markers were correlated with survival in various cancers 23 , 25 - 27 . Similarly, ALB alone or based markers were confirmed as independent predictors of PDAC with poor survival 14 , 28 , 29 . ALP associated with ALB as a predictor had been applied into several other cancers 19 , 30 , however, the value of prediction in PDAC was still not identified.…”
Section: Introductionmentioning
confidence: 79%
“…This indicated inflammation was obviously related to the tumorgenesis of PDAC 10 , 11 . Furthermore, many studies had identified inflammation-based scores as prognostic indicators of PDAC, such as neutrophil-lymphocyte ratio (NLR), C-reactive protein/albumin (CRP/Alb) ratio, platelet-to-albumin ratio (PAR) and lymphocyte-to-monocyte ratio (LMR) 4 , 12 - 14 . Therefore, it is quite reasonable to further excavate inflammation-based score for prognostic prediction of PDAC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on this topic were identified by the search, but most were excluded because of the number of tumours not resected or the absence of model performance measures. The included studies of Shirai and colleagues (platelet and albumin) and Numata et al . (Glasgow Prognostic Score and CA19.9) showed reasonable performance.…”
Section: Discussionmentioning
confidence: 99%
“…Although a series of inflammation-based scores appeared to be prognostic factors in diverse malignances 3,32 , inflammation factors were failed to be incorporated into AJCC 8th staging system or other existed predictive model in PDAC. Intriguingly, AJCC 8th staging system integrating poNLR in Table 3 indicated that the incorporated nomograms led to higher C-indices than that of AJCC 8th staging system alone.…”
Section: Discussionmentioning
confidence: 99%